Pengaruh Substitusi Cuka dengan Sari Buah Delima terhadap Karakteristik Fisikokimia, Kualitas Sensoris, dan Aktivitas Antioksidan Mayones - Jennifer Callysta Thee; Nyoman Puspa Asri; Joko Sulistyo (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aimed to evaluate the effect of substituting vinegar with pomegranate juice (PJ) on the physicochemical characteristics, sensory quality, and antioxidant activity of mayonnaise. The mayonnaise was formulated into five treatments with varying concentrations of vinegar and PJ. The analyzed parameters included pH, color (L*, a*, b*), viscosity, emulsion stability, and sensory attributes (taste, aroma, color, texture, and preference), while antioxidant activity was assessed in the best formulation. The results showed that increasing the PJ substitution significantly improved viscosity and emulsion stability, decreased lightness (L*), and enhanced the red hue (a*). The P4 formulation (containing 2.75% PJ) demonstrated the best overall performance, with high viscosity, excellent emulsion stability, and also receiving high sensory scores. Antioxidant analysis revealed that P4 had higher antioxidant activity compared to the control (P0). Therefore, PJ has the potential to serve as a natural alternative to vinegar in mayonnaise production while enhancing the product's stability and functional value.